2009
DOI: 10.1038/ajg.2009.322
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated With Common Therapy Regimens for Moderate-to-Severe Crohn's Disease

Abstract: Treatment with steroids, ISs, or anti-TNF agents singly and in combination in patients with CD is associated with increased risks of infection, demyelinating disorders, and cervical dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 27 publications
5
138
0
4
Order By: Relevance
“…A similar study on 410 patients treated with MP revealed a 14% rate of infectious complications, including pneumonia in 3.9% and herpes zoster in 3%. A recent publication looking at over 22,000 patients with CD found a higher rate of infection with tuberculosis, herpes zoster, sepsis (as well as demyelination and cervical dysplasia) amongst patients on thiopurines, which is increased by combined regimens of immunomodulation with steroids and/ or anti-TNF-a agents [Marehbian et al 2009]. Hepatitis B infection is looked at in greater detail later in the article.…”
Section: Infectionmentioning
confidence: 99%
“…A similar study on 410 patients treated with MP revealed a 14% rate of infectious complications, including pneumonia in 3.9% and herpes zoster in 3%. A recent publication looking at over 22,000 patients with CD found a higher rate of infection with tuberculosis, herpes zoster, sepsis (as well as demyelination and cervical dysplasia) amongst patients on thiopurines, which is increased by combined regimens of immunomodulation with steroids and/ or anti-TNF-a agents [Marehbian et al 2009]. Hepatitis B infection is looked at in greater detail later in the article.…”
Section: Infectionmentioning
confidence: 99%
“…Safety concerns associated with anti-TNF-alpha agents have been documented in the literature and include serious and opportunistic infections, tuberculosis, and hematologic malignancies. [22][23][24][25] However, randomized clinical trials found rates of serious adverse events to be similar between biologic agents and placebo, and a study of adalimumab in clinical practice found rates of adverse events consistent with clinical trials. 22,[28][29][30][31][32][33] The results of this real-world analysis found …”
Section: Concomitant Treatment For CD Patients Treated With Iv Versusmentioning
confidence: 99%
“…[18][19][20][21] The reported potential adverse events include infection-most notably tuberculosis, sepsis, and candidiasis-with reports of malignancies and hepatic toxicities. 16,[22][23][24][25][26] In a study of certolizumab, with a 26-week follow-up, malignancies were reported in 4 patients-2 each in the 331 patients in the certolizumab group and in the 328 patients in the placebo group. 16 A systematic review of all infliximab trials concluded that 0.5% of patients treated with infliximab developed malignancies compared with 0.06% in the placebo group.…”
Section: Patient Selectionmentioning
confidence: 99%
“…[82] The risk of severe sepsis increases further if combination immunosuppressants (such as combinations of azathioprine and anti-TNF agents) are used. [83] The TREAT registry showed that while unadjusted analysis indicated that Infliximab is associated with an increased risk of infection, multivariate logistic regression analysis suggested that Infliximab was not an independent predictor of serious infections and the increased risk was associated with disease severity and concomitant prednisone use. [84] The REACH study, evaluating the efficacy of Infliximab in children with moderate to severe CD refractory to immunomodulatory treatment, reported serious infections as the major adverse events with their frequency being higher with shorter treatment intervals.…”
Section: Immunosuppressants In Ibdmentioning
confidence: 99%